On transurban flows in Irkutsk - Grigoryeva , Elena; Lidin, Konstantin (project baikal, 2025)
The article considers the links between designed and built-up areas and the state of pedestrian flows in the city centre through the example of Irkutsk. Taking into account the specifics of Irkutsk, where students and teachers of numerous universities play a significant role, it is proposed to extend the Green Diameter to the left-bank inter-university campus. The authors update the proposal to solve the identified problem by building a pedestrian and cycle bridge across the Angara River and clearing the main axes of the city – the Baikal Ray and the Green Diameter perpendicular to it.